2021
DOI: 10.1002/mds.28828
|View full text |Cite
|
Sign up to set email alerts
|

The South African Parkinson's Disease Study Collection

Abstract: Parkinson's disease (PD) incidence is increasing in sub‐Saharan Africa. We recruited 687 individuals with PD from different ancestral groups across South Africa. More Afrikaner Europeans had early‐onset PD than other ancestral groups. More men had PD than women, with a younger age at onset for men (56 years).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A recent South African study involving 687 cases of PD in mixed race persons reported an onset age of 57.3 years. For the subgroup of 102 persons of African ancestry, the age at onset was 54.8 years [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent South African study involving 687 cases of PD in mixed race persons reported an onset age of 57.3 years. For the subgroup of 102 persons of African ancestry, the age at onset was 54.8 years [ 8 ].…”
Section: Introductionmentioning
confidence: 99%